Efflux-Mediated Antimicrobial Resistance in Bacteria 2016
DOI: 10.1007/978-3-319-39658-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Drug Efflux Pumps in Enterobacter and Klebsiella

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 149 publications
0
11
0
Order By: Relevance
“…Efflux also affects biocidal agents comprising disinfectants, antiseptics, and preservatives that are commonly practiced in medicine [11,12]. Moreover, it is also involved in bacterial colonization and virulence [10,[13][14][15][16] and contributes to the acquisition of additional mechanisms of resistance that includes the mutation in antibiotic targets (e.g. mutation in gyrase/topoisomerase for quinolone) or the production of enzymes that degrade antibiotics (e.g.…”
mentioning
confidence: 99%
“…Efflux also affects biocidal agents comprising disinfectants, antiseptics, and preservatives that are commonly practiced in medicine [11,12]. Moreover, it is also involved in bacterial colonization and virulence [10,[13][14][15][16] and contributes to the acquisition of additional mechanisms of resistance that includes the mutation in antibiotic targets (e.g. mutation in gyrase/topoisomerase for quinolone) or the production of enzymes that degrade antibiotics (e.g.…”
mentioning
confidence: 99%
“…Also, resistance to third-generation cephalosporin in Enterobacteriaceae is always associated with ESBL, whereas resistance to carbapenems can be caused by production of an ESBL or plasmid mediated coded AmpC cephalosporinase combined with an efflux pump system or a decrease in outer membrane permeability [ 35 – 37 ]. It is reported that the mutation rate of the membrane permeability of Enterobacteriaceae is relatively high [ 38 , 39 ], so when dealing with meningitis caused by EPE, even if it is treated with carbapenem antibiotics, good clinical outcomes may not be obtained. All of the 220 cases of Enterobacteriaceae in this study were sensitive to polymyxin B, which maybe the last line of defence against EPE or Carbapenem-resistant Enterobacteriaceae (CRE).…”
Section: Discussionmentioning
confidence: 99%
“…K. pneumoniae K. pneumoniae comes after E. coli, the main enterobacterial species involved in nosocomial infections, with the highest proportion of isolates producing plasmid-mediated extended-spectrum β-lactamases and carbapenemases [40][41][42][43]. Two major RND pumps and their regulatory elements are characterized in K. pneumoniae, AcrAB and OqxAB [40,44]. The oqxAB operon was originally described on plasmid carried by an E. coli strain conferring resistance to chloramphenicol and quinolones [44].…”
Section: Enterobacteriaceaementioning
confidence: 99%